2008
DOI: 10.1242/jcs.019166
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of PI3K signalling by the phosphatidylinositol transfer protein PITPα during axonal extension in hippocampal neurons

Abstract: Supplementary material available online at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 40 publications
3
44
0
Order By: Relevance
“…Previous works have proved that BDNF facilitates axon elongation through BDNF/TrkB signaling (42,48,49). In this study, we found that BDNF had no effect on axonal elongation when LIMK1 was knocked down by siRNA, and BDNF stimulation further enhanced axonal growth in primary neurons transfected with wild-type LIMK1, suggesting that BDNF could induce axonal elongation in a manner dependent on LIMK1 activity.…”
Section: Discussionsupporting
confidence: 47%
“…Previous works have proved that BDNF facilitates axon elongation through BDNF/TrkB signaling (42,48,49). In this study, we found that BDNF had no effect on axonal elongation when LIMK1 was knocked down by siRNA, and BDNF stimulation further enhanced axonal growth in primary neurons transfected with wild-type LIMK1, suggesting that BDNF could induce axonal elongation in a manner dependent on LIMK1 activity.…”
Section: Discussionsupporting
confidence: 47%
“…Akt has also been implicated in synaptogenesis (Akama & McEwen, 2003) and synaptic transmission (Wang, et al, 2003). Others have found the pathway to be essential for elongation, guidance and branching of both axons and dendrites (Cosker, et al, 2008;Luikart, et al, 2008). These findings are consistent with the widespread distribution of Akt in the central nervous system.…”
Section: Cc2d1a and Akt Functionsupporting
confidence: 61%
“…This may be a counterpart to the elaboration of multiple axons in the hippocampal paradigm outline above. Normally, GSK-3 inhibition and APC plus-end binging are localized to the axon growth cone downstream of PI3K signaling (Eickholt et al 2002;Zhou et al 2004;Cosker et al 2008). More general inhibition of GSK-3 may induce multiple foci along the axon capable of supporting efficient tubulin polymerization, thus resulting in branching.…”
Section: Gsk-3 and Axon Elongationmentioning
confidence: 99%